Innovation-Led Governance and Growth: Narrative of Transforming India - Gurwinder Kaur (Journal of Women Entrepreneurship & Business Management (e-ISSN: 2583-8210), 2025)
Mission innovation seeks to establish a new purpose, mission, or philosophy in the organization. The mission-based approach aims to increase the effectiveness of public initiatives by encouraging practical, multi-sectorial, and multi-disciplinary governance. This article analyses how the Innovation Mission evolved in India and assesses how the Atal Innovation Mission has affected social change and the Atal New India Challenges. It also evaluates the Atal Innovation Mission’s capacity for creativity and looks at the governance’s innovation-driven strategy, especially since 2014. This study uses content analysis to investigate Indian innovation. It uses information from the Atal Innovation Mission’s (AIM) official website, which is run by the Indian government’s NITI Aayog. The paper suggests that mission-driven approaches enhance the nation’s innovation capacity significantly, while also contributing to broader social outcomes improved socioeconomic conditions, financial empowerment of women, and expanded commercial opportunities for underrepresented communities.